PIALUNG: THE UNEXPLORED KAPAMPANGAN VERSIONS OF SOME FILIPINO CULTURAL GAMES - Tubera, Joel G.; Yumang, Paul Henry (Program Pascasarjana Universitas Negeri Jakarta, 2015)
Filipino games are integral part of our physical education curriculum. They are meant to promote fitness while preserving and promoting their cultural value. The Physical Education class is expected to provide venue and opportunities for students to enjoy and appreciate cultural games while understanding the Philippine heritage in general. However, the impact of globalization in many of our ways forced Filipinos to embrace both foreign and technology based games and physical activities. It can be observed that many of our cultural games slowly losses their place in the playing arena of many children specially those who lives in the urban areas. The study revisited and recorded some unexplored Kapampangan versions of some Filipino cultural games enjoyed in the past. Interview, brainstorming, participant observation and video recording were used to achieve the objective of the study which is descriptive and ethnographic in nature. Purposive sampling was utilized to select elderly Kapampangans who became the primary source of information. Physical Education teachers were also used to evaluate the potential of the games for P.E class utilization. The games were described as to; Title of the game, Fitness components, Pre-games, Players, Equipment, Playing Area, Objectives and Procedure. The 20 collected games were classified accordingly. The study proves that it is not yet late to start reviving the cultural games and if properly presented, they can be used in improving fitness and promoting social values and awareness. It is recommended that schools should start to organize their own cultural game festival. Government and non-government organizations could also support similar endeavors to fully preserve and promote the collected cultural games.